Female mice may have exacerbated catabolic signalling response compared to male mice during development and progression of disuse atrophy. Issue 3 (5th March 2021) - Rosa‐Caldwell, Megan E.; Lim, Seongkyun; Haynie, Wesley A.; Brown, Jacob L.; Deaver, John William; Morena Da Silva, Francielly; Jansen, Lisa T.; Lee, David E.; Wiggs, Michael P.; Washington, Tyrone A.; Greene, Nicholas P.
Abstract: Background: Muscle atrophy is a common pathology associated with disuse, such as prolonged bed rest or spaceflight, and is associated with detrimental health outcomes. There is emerging evidence that disuse atrophy may differentially affect males and females. Cellular mechanisms contributing to the development and progression of disuse remain elusive, particularly protein turnover cascades. The purpose of this study was to investigate the initial development and progression of disuse muscle atrophy in male and female mice using the well‐established model of hindlimb unloading (HU). Methods: One hundred C57BL/6J mice (50 male and 50 female) were hindlimb suspended for 0 (control), 24, 48, 72, or 168 h to induce disuse atrophy (10 animals per group). At designated time points, animals were euthanized, and tissues (extensor digitorum longus, gastrocnemius, and soleus for mRNA analysis, gastrocnemius and extensor digitorum longus for protein synthesis rates, and tibialis anterior for histology) were collected for analysis of protein turnover mechanisms (protein anabolism and catabolism). Results: Both males and females lost ~30% of tibialis anterior cross‐sectional area after 168 h of disuse. Males had no statistical difference in MHCIIB fibre area, whereas unloaded females had ~33% lower MHCIIB cross‐sectional area by 168 h of unloading. Both males and females had lower fractional protein synthesis rates (FSRs) within 24–48 h of HU, and females appeared to have a greater reduction compared with males within 24 h of HU (~23% lower FSRs in males vs. 40% lower FSRs in females). Males and females exhibited differential patterns and responses in multiple markers of protein anabolism, catabolism, and myogenic capacity during the development and progression of disuse atrophy. Specifically, females had greater mRNA inductions of catabolic factors Ubc and Gadd45a (~4‐fold greater content in females compared with ~2‐fold greater content in males) and greater inductions of anabolic inhibitors Redd1 and Deptor with disuse across multiple muscle tissues exhibiting different fibre phenotypes. Conclusions: These results suggest that the aetiology of disuse muscle atrophy is more complicated and nuanced than previously thought, with different responses based on muscle phenotypes and between males and females, with females having greater inductions of atrophic markers early in the development of disuse atrophy.